Catalytic upgrading of bio-oil produced from hydrothermal liquefaction of Nannochloropsis sp. (March 2018) - Shakya, Rajdeep; Adhikari, Sushil; Mahadevan, Ravishankar; Hassan, El Barbary; Dempster, Thomas A.
Highlights: Upgrading of algae bio-oil was performed using five catalysts at 300 and 350 °C. High yield of upgraded bio-oil was observed at 300 °C. 65 to 75% decrease in nitrogen content was obtained with catalytic runs at 350 °C. Ru/C and Pt/C gave a better quality upgraded bio-oils. 35–40% of the upgraded bio-oils were in diesel range. Abstract: Upgrading of bio-oil obtained from hydrothermal liquefaction (HTL) of algae is necessary for it to be used as a fuel. In this study, bio-oil obtained from HTL of Nannochloropsis sp. was upgraded using five different catalysts (Ni/C, ZSM-5, Ni/ZSM-5, Ru/C and Pt/C) at 300 °C and 350 °C. The upgraded bio-oil yields were higher at 300 °C; however, higher quality upgraded bio-oils were obtained at 350 °C. Ni/C gave the maximum upgraded bio-oil yield (61 wt%) at 350 °C. However, noble metal catalysts (Ru/C and Pt/C) gave the better upgraded bio-oils in terms of acidity, heating values, and nitrogen values. The higher heating value of the upgraded bio-oils ranged from 40 to 44 MJ/kg, and the nitrogen content decreased from 5.37 to 1.29 wt%. Most of the upgraded bio-oils (35–40 wt%) were in the diesel range. The major components present in the gaseous products were CH4, CO, CO2 and lower alkanes.